A pairwise-based approach to examining the Feldstein–Horioka condition of international capital mobility (2016)
We propose a pairwise procedure to test the Feldstein–Horioka condition of capital mobility. In contrast to the existing approach, we explicitly examine the relationship between domestic investment and foreign savings rather than domestic savings. In terms of addressing the Feldstein–Horioka puzzle, our results based on a panel of OECD and emerging market economies initially suggest that the depth and extent of capital mobility remain generally limited and that mobility has increased over the past 20 years. However, in contrast to existing studies, we find that capital mobility between Euro and EU pairs is more extensive than between pairs that involve other countries. If our sample is expanded to include emerging markets, we find that capital mobility has also increased though is weaker than for OECD economies. We provide additional insight in terms of consistency between our assessment of capital mobility based on the Feldstein–Horioka condition (a quantity approach) and a price approach based on real interest rate differentials. © 2015, Springer-Verlag Berlin Heidelberg.